KEPENTINGAN INDONESIA MELAKUKAN KERJASAMA DENGAN SELANDIA BARU DALAM BIDANG ENERGI GEOTHERMAL - Mellia Indri; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research discusses about cooperation on New Zealand in Indonesia in in the field of geothermal energi. Indonesia is one country with the greatest potential for geothermal energi in the world. As a renewable and environmental friendly energi , geothermal energi potential need to be improved its contribution to meet domestic energi needs which will reduce Indonesia's dependence on fossil energi sources dwindling. Although the potential of Indonesia has big geothermal energi , but the utilization of geothermal energi is not maximized.Indonesia decided to cooperate with New Zealand in order to maximize the utilization of geothermal energi .In this research, the writer uses library research technique. Sources were obtained from journals, website and news.Method that applied in this research is qualitative. This research also uses level of analysis of nation-state and neo-liberalism perspective. Theory of cooperationwill supports to explain the problem in this research.There are two factor behind Indonesia and New Zealand partnership. First, internal factor which geothermal resources in Indonesia has not been maximalize. This geothermal development will increase energy reserves and able to keep Indonesia’s energy security.Second. external factor which. New Zealand is a country with high experiences and high capabilities in geothermal development. New Zealand is also known as the state which has advantages and capabilities in geothermal technology and geothermal human resources.Keywords: cooperation, investment, energi, geothermal, interest